Pharmaco-induced nefrotoxicity - Ciraque, Aline; Silva, Claudia Maria Correia e; Silva, Aline Santana da (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Farmácia, 2022)
The kidneys are extremely important organs for carrying out various functions in the body, some imbalances can lead to renal failure, which can be chronic kidney failure (CRF) or acute kidney failure (AKI). AKI is common in hospitalized patients, especially those who have some comorbidities, due to the use of nephrotoxic drugs. According to the risk factors, patients with a tendency to develop ARF by drugs can be identified and preventive measures must be taken in order to avoid complications for the patient. Medicines such as aminoglycoside antibiotics, polymyxins, non-steroidal anti-inflammatory drugs and contrast agents have nephrotoxic potential, these classes act by different mechanisms that impair renal function and are widely used. When there is no possibility of changing the class to treat a certain pathology, certain measures must be taken for a reduced hospital stay and prevent serious complications due to nephrotoxicity, since it can be lethal.